Pengaruh Current Ratio, Debt Equity Ratio Dan Debt To Asset Ratio Terhadap Return On Asset Pada Koperasi di Kota Palembang - Mutiara Aulia; Harsi Romli; Luis Marnisah (Program Magister Manajemen Indo Global Mandiri University, 2020)
The objective of this research was to determine and analyze how the effect of Current Ratio, Debt Equity Ratio and Debt To Asset Ratio on Return On Assets of Cooperatives in Palembang City. The research sample comprised of 30 cooperatives financial reports with a total of 6 observations for 5 years and selected by purposive sampling. The data analysis technique used was linear regression analysis techniques. In this research, the liquidity variable was measured using the Current ratio, debt was measured using Debt to Equity Ratio, debt ratio was measured using Debt to total asset ratio and Profitability was measured using Return On Assets (ROA). The hypothesis testing used was multiple analysis techniques with the SPSS version 23 application. The results showed that CR partially had a positive and significant effect on ROA. While partially DER had a negative and significant effect on ROA. Partially DAR had a negative and significant effect on ROA Simultaneously, the effect of CR, DER, and DAR had a positive and significant effect on ROA with a coefficient of determination (R2) of 67.2% while the remaining 32.8% was affected by other variables.